Ultra-high optomechanical EUV-hypersound coupling rate in phoxonic crystal structures based on 2D MWCNTs array - Yasser Shamsollahi; Mohammad Kazem Moravvej-Farshi (Scientific Reports)
Abstract We have studied the optomechanical properties of phoxonic crystals based on multiwall carbon nanotubes (MWCNT) theoretically and demonstrated that optical waves in the range of extreme ultraviolet (EUV—i.e., several PHz) interact with hypersonic (several GHz) mechanical waves excited in surface acoustic wave (SAW) devices. We have shown the possibility of obtaining optomechanical coupling rates in the range of 2.78 to 63.56 THz nm−1, which is at least an order of magnitude higher than those reported to date. Such ultra-high coupling rates are achievable by utilizing an array of high aspect ratio CNTs with nanometer spacing to produce photonic and phononic crystal structures such as cavities and waveguides known as phoxonic crystals. We also show how mode analysis could be utilized to recognize pattern disorders of experimentally grown MWCNT arrays.